2020
DOI: 10.1007/s00414-020-02384-z
|View full text |Cite
|
Sign up to set email alerts
|

TMEM119 as a specific marker of microglia reaction in traumatic brain injury in postmortem examination

Abstract: The aim of the present study was a refined analysis of neuroinflammation including TMEM119 as a useful microglia-specific marker in forensic assessments of traumatic causes of death, e.g., traumatic brain injury (TBI). Human brain tissue samples were obtained from autopsies and divided into cases with lethal TBI (n = 25) and subdivided into three groups according to their trauma survival time and compared with an age-, gender-, and postmortem interval-matched cohort of sudden cardiovascular fatalities as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…It was also found that Cx3cr1, Trem2, Tyrobp, Cd33, Sall1, Tmem119, Siglec-H, Iba1, and P2ry12 specifically expressed in mouse microglia (Chiu et al, 2013;Galatro et al, 2017). Recently, another microglia specific marker Tmem119 has been identified as a marker of mature microglia in the brain (Bennett et al, 2016;Satoh et al, 2016;Bohnert et al, 2020) and Siglec-H expression specific to activated microglia where it cause phagocytosis of glioma cells of brain tumor (Kopatz et al, 2013;Konishi et al, 2017) and Olfml3 as a new Tgf-β1/Smad2 target gene in microglia (Neidert et al, 2018) has been reported. However, detailed studies on targeting these identified genes to understand microglia function in the regulation of oxidative stress and neurodegeneration are still elusive.…”
Section: Signature Genes Of Microgliamentioning
confidence: 95%
“…It was also found that Cx3cr1, Trem2, Tyrobp, Cd33, Sall1, Tmem119, Siglec-H, Iba1, and P2ry12 specifically expressed in mouse microglia (Chiu et al, 2013;Galatro et al, 2017). Recently, another microglia specific marker Tmem119 has been identified as a marker of mature microglia in the brain (Bennett et al, 2016;Satoh et al, 2016;Bohnert et al, 2020) and Siglec-H expression specific to activated microglia where it cause phagocytosis of glioma cells of brain tumor (Kopatz et al, 2013;Konishi et al, 2017) and Olfml3 as a new Tgf-β1/Smad2 target gene in microglia (Neidert et al, 2018) has been reported. However, detailed studies on targeting these identified genes to understand microglia function in the regulation of oxidative stress and neurodegeneration are still elusive.…”
Section: Signature Genes Of Microgliamentioning
confidence: 95%
“…As already mentioned in previous publications, a special role as a stimulus of the resident microglia was attributed to the released myelin after damage of the myelin sheath with subsequent activation [ 57 , 58 ]. In addition to a very early response of microglia after TBI, one of our own publications also showed activation of the so-called M2 microglia/macrophages, which contribute to the regeneration of injured brain tissue through their phagocytic activity [ 19 ]. Demyelination, such as after TBI, results in an increased release of lipid components such as phospholipids and cholesterol, which are major constituents of myelin and are phagocytosed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to forensic neuropathological diagnostic methods, Benjamin Ondruschka and Michael Bohnert contributed equally to this work. postmortem biochemical analyses of various cytokines, acute phase proteins, CNS biomarkers [7,[13][14][15][16][17], or Na + -glucose transporters [18] in CSF and brain tissue as well as investigations of the early tissue reaction of local microglia after trauma are meanwhile increasingly performed [19]. Furthermore, the applicability of immunocytochemical staining in postmortem CSF could be demonstrated [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglia simultaneously express several hallmarks, such as Iba1, Cx3cr1, P2ry12, Tmem119, Trem2, Cd11b, Hexb, Csf1r, Itgam, and Siglec , among others [ 38 , 39 , 40 , 41 , 42 , 43 ]. However, there is no unique expression pattern of these transcripts in these cells, that is, it varies according to the pathological condition, age, sex, species, and brain area [ 27 ].…”
Section: Microglial Heterogeneity In the Hypothalamusmentioning
confidence: 99%